2023
DOI: 10.3390/reactions4040038
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Biomass-Derived Molecules into Alkyl Levulinates Using Heterogeneous Catalysts

Nobutaka Yamanaka,
Shogo Shimazu

Abstract: Alkyl levulinates are promising and versatile biomass-derived chemicals, which are utilized as fuel additives, flavoring agents, fragrances, solvents, and precursors for synthesizing valuable γ-valerolactone. A method for synthesizing alkyl levulinates involves the esterification of levulinic acid with the corresponding alkyl alcohols in the presence of solid acid catalysts that have abundant Brønsted acid sites. Alkyl levulinates can also be synthesized from other biomass-derived molecules such as furfuryl al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Heterogeneous acid catalysts can be easily separated and reused at the end of the reaction cycle. Several catalysts, such as heteropolyacids, metal oxides, zeolites, and ionic liquids, were used to produce ethyl levulinate [ 43 , 44 , 45 ]. However, the synthesis of these catalysts turns out to be very expensive and requires long reaction times, adversely affecting the cost of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous acid catalysts can be easily separated and reused at the end of the reaction cycle. Several catalysts, such as heteropolyacids, metal oxides, zeolites, and ionic liquids, were used to produce ethyl levulinate [ 43 , 44 , 45 ]. However, the synthesis of these catalysts turns out to be very expensive and requires long reaction times, adversely affecting the cost of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that base-mediated enhanced proton transfer through a water bridge causes stabilization of the transition state in the H 2 heterolysis rate-determining reaction step. Ghorbanpour et al showed that in the reaction of decomposition of formic acid, more hydrogen gas is released when sodium formate is used. , Alkyl levulinates (ALs) are biomass-based chemicals with many applications in various fields and can replace chemicals produced from petrochemical pathways. Among the uses of ALs, one can mention their role as a solvent, additive, and precursor in producing gamma-valerolactone (GVL). Ethyl levulinate (EL) is an ester with a fruity odor and can be prepared from levulinic acid (LA) or the reaction between furfuryl alcohol and ethanol. Considering the existence of various sources for EL production, it can be pointed out that this combination is a suitable option for biofuel additives .…”
Section: Introductionmentioning
confidence: 99%